SMARTPHONE PURCHASING DECISION MAKING USING AN INTERVAL-VALUED INTUITIONISTIC FUZZY AHP APPROACH: A CASE STUDY IN MALANG CITY - Noor Hidayat; Vira Hari Krisnawati; Sobri Abusini; Desfi Rahmatul Khairi (PATTIMURA UNIVERSITY, 2026)
The advancement of communication technology, particularly in the smartphone industry, has significantly influenced consumer purchasing behavior. This study aims to analyze the priority criteria in smartphone purchasing decisions using the Interval-valued Intuitionistic Fuzzy Analytic Hierarchy Process (IVIF-AHP) method. Data was collected through interviews with three experts in the smartphone industry in Malang City. The analysis results showed that camera quality had the highest weight of , followed by RAM/storage capacity with a weight of , and the multiple SIM feature with a weight of . Although battery life and pricewere also considered, they had lower weights of and , respectively. These findings indicate that consumers prioritize features and quality over price. The application of the IVIF-AHP method allows handling uncertainty and produces more realistic priority weights that can be directly applied in marketing decision-making. This study also provides strategic implications for smartphone manufacturers: focus on promoting camera features and device performance, and consider the multiple-SIM feature in specific markets. In the future, adding other criteria, such as brand or screen size, could provide more comprehensive insights into decision-making.